Effect of tank colour on larval performance of the Amazon River prawn Macrobrachium amazonicum - Maciel, Cristiana Ramalho; Valenti, Wagner C. [UNESP] (Wiley-Blackwell, 2014)
The aim of this study was to evaluate the effects of hatchery-tank colours (white, yellow, red, blue, green and black) on the performance of larval culture of Macrobrachium amazonicum. The larvae were fed daily with newly hatched Artemia nauplii. The hatchery-tank colours affected the light level inside the tanks, the consumption of Artemia nauplii (AN), larval development, survival, mass gain and productivity of postlarvae (PL). The overall consumption of Artemia nauplii per larva during the larval cycle was 30% and 45% higher in the green and red tanks respectively. The significant variation of AN consumption among tank colours (P= 0.0006) indicates that M. amazonicum larvae are visual predators. Survival was higher in the black, blue and green tanks, reaching more than 75%. However, the highest productivity was obtained in the black tanks (80.1 PLL-1). Lighter coloured tanks and excess luminosity (more than 2 mu mols(-1)m(2) at tank bottom) appear to be important stress factors for larvae, contributing to reduce survival and productivity. The results indicate that rearing M. amazonicum in black tanks will improve larvae condition, ensure greater productivity of postlarvae and lower Artemia consumption, increasing technological and economic viability.
Keywords: predator-prey; productivity; Amazon River prawn; tank colour